Determination of Wind Turbine Main Bearing Load Distribution. (May 2019) - Kock, S.; Jacobs, G.; Bosse, D.
Abstract: The presented paper introduces simulative method for the determination of load and pressure distribution in the main roller bearings in multi-MW wind turbines. This method has been developed using the example of a generic 6 MW research wind turbine (WT). The investigated drive train comprises of a main gearbox and is mounted with a four point suspension. The fixed rotor bearing is a spherical roller bearing and the floating rotor bearing is a cylindrical roller bearing. The load and pressure distribution is determined by finite element (FE) simulation under consideration of real hub loads and elastic surroundings. The hub loads have been calculated using Multibody Simulation. Three different rotor bearing models are introduced, which consider FE contact conditions, macro-geometry, stiffness and rolling element profile. The developed method is transferable to different rolling bearing types and can be used to improve bearing load and pressure distribution in multi-MW WTs under consideration of elastic surroundings (main shaft, frame and bearing housing).